Analysing the Pesantren Tradition of Arranged Marriages from the â€œKupi Fatwa Trilogyâ€ Perspective - Rasidin, Mhd.; Witro, Doli; Busni, Darti; Nurjaman, Andri; Afan, Marjai (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This article aims to analyze the phenomenon of arranged marriage traditions in the Islamic boarding school world from the perspective of the KUPI fatwa trilogy. The KUPI fatwa trilogy, namely the maâ€™rÅ«f (kindness), mubÄdalah (reciprocity), and true justice approaches, is used to investigate the phenomenon of arranged marriage traditions in the world of Islamic boarding schools. This article uses a library research method with a phenomenological approach which is analyzed using the KUPI fatwa trilogy. Therefore, the nature of this research is descriptive-analytical. Then data collection techniques come from primary and secondary materials. Meanwhile, the analysis technique uses Miles and friendsâ€™ qualitative data analysis techniques, which consist of data condensation, data presentation, and drawing conclusions. The research results show that the tradition of matchmaking in the Islamic boarding school world has given rise to two characters and models of matchmaking in the Islamic boarding school world, firstly the one-way matchmaking tradition which is coercive, and secondly the two-way matchmaking tradition which is not coercive. Salafi Islamic boarding schools which are still conservative still carry out the tradition of one-way matchmaking which is coercive and one-sided, by denying women the opportunity to participate and hear their opinions regarding matchmaking. This results in injustice and tyranny towards women, so the tradition of this type of arranged marriage is contrary to the KUPI fatwa trilogy, because women are positioned as objects rather than equal subjects. However, it should be noted that not all Islamic boarding schools follow the custom of one-way arranged marriage, instead, there is a more egalitarian custom known as two-way arranged marriage, where women are treated as subjects with the same rights and freedoms as men. This is in line with the KUPI fatwa trilogy, because the practice of matchmaking like this is a tradition of fair matchmaking and supports women in order to give birth to maâ€™rÅ«f (kindness), mubÄdalah (reciprocity), and true justice. The Miftahul Huda II Bayasari Ciamis Islamic Boarding School is one of the Islamic boarding school institutions that perpetuates the tradition of two-way matchmaking which is non-coercive and in accordance with the spirit of the KUPI fatwa trilogy.